Modeling and Optimizing Lecturer Professional Commitment: A Culturally Rooted Approach Using the POP-SDM Framework - Zainuri, Zainuri; Setyaningsih, Sri; Herfina, Herfina (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
Growing demands for higher education quality require universities to model and optimise lecturers’ professional commitment through culturally rooted approaches. This study explores how local wisdom can enhance professional commitment among lecturers at Pancasila University, using the POP-SDM (Professional Organisational Performance-Human Resource Management) framework. It examines the relationship among local wisdom, organisational culture, and professional development in fostering greater commitment to teaching and academic responsibilities. Data was gathered through surveys and interviews with lecturers, followed by statistical analysis to identify key factors influencing professional commitment. The findings emphasise the significance of integrating local cultural values into the academic environment to improve lecturers’ job satisfaction, performance, and commitment. This research offers strategies to enhance lecturer professionalism in Indonesian higher education institutions and demonstrates how local wisdom can be applied in modern academic settings. By incorporating indigenous knowledge, the study shows that local wisdom not only strengthens professional commitment but also enriches the broader institutional culture, fostering a deeper connection between educators and the communities they serve. This model offers a sustainable approach for improving academic professionalism and institutional performance across Indonesian universities.